Trastornos mentales en médicos y enfermeras de primera línea de atención al covid-19 en el hospital general docente - Mayorga Mayorga, Jairo Israel (2025)
The COVID-19 pandemic represents a health crisis that affects the physical and mental health of people in Ecuador and the world. It is important to consider the necessity of adopting health care practices in the occupational environment and reflect it on administrative shortcomings of health systems for the protection of occupational health. The present study was carried out with 235 professionals, medical and nursing staff exposed to COVID-19 who worked extended hours of 12 hours during the period May-September 2020 at the Hospital General Docente of Ambato. The research was developed as a cross-sectional descriptive observational study, the data were collected using PFI, DASS-21 and ISI questionnaires, to obtain information on the percentages of incidence of job satisfaction and job exhaustion, as well as their correlation with indicators. occupational health: stress, depression, anxiety and insomnia with the gender and profession of the population. The existence of a significant correlation between gender and the degree of job exhaustion was determined; the female population presented higher levels of exhaustion compared to the male gender, at the same time, the nursing staff who worked on the front line of care COVID-19 patients presented a higher incidence of mild insomnia associated with stress, depression and anxiety. However, job satisfaction levels remained at satisfactory levels (76.6%), which demonstrates the personal involvement of professionals in the face of the pandemic.